Acute complicated diverticulitis is associated with an increased advanced neoplasia diagnosis rate: A retrospective study on 1852 patients. Issue 5 (5th February 2021) - Abu Baker, Fadi; Ganayem, Mohanad; Mari, Amir; Taher, Randa; Suki, Mohamad; Kopelman, Yael
Abstract : Abstract: Recent reports have documented an unchanged rate of occurrence of colorectal cancer (CRC) and have publicised doubts regarding the benefit of prompt colonoscopy procedures after an episode of acute diverticulitis (AD). These reports mandate further evaluation of colonoscopy yield and timing in this regard. The current study aims to determine whether the rate of advanced colonic neoplasia after AD differs from that of average-risk patients, and to identify risk factors that are associated with their development. In this retrospective study, we included all patients who had been hospitalized to the surgery ward in the years 2008 to 2016 with radiographically confirmed AD, and had completed colonoscopies within one year of index hospitalization. Patients who were referred for screening colonoscopies during the same years were included as a control group. We compared the rates of diagnosis of CRC and advanced polyps for both groups before and after adjustment for multiple confounders. Moreover, we investigated risk factors that were associated with increased rate of advanced neoplasia diagnosis. A total of 350 patients were included in the AD group and 1502 patients in the screening colonoscopy control group. The CRC diagnosis rates (1.7% vs 0.3%; P  = .09) and overall diagnosis rates of advanced neoplasia (12.3% vs 9.6%; P  = .19) were not significantly different when findings were compared between the AD and control groups, respectively. Cases of complicated diverticulitis, however, were associated with increased risk of advanced neoplasia diagnosis (odds ratio (OR) 3.729, 95% confidence interval (CI) 1.803–7.713; P  = .01). The diagnosis rate for advanced neoplasia after AD was not significantly different from that of average-risk populations. A course of complicated AD, however, was a potential risk factor.